Johannes 19,25—27 - Zumstein, Jean (Zeitschrift für Theologie und Kirche, 1997)
John 19: 25—27 should be viewed as a symbolic text which deals with the future of the members of Jesus' family after the 'lifting up'. In a typical Johannine manner, the scene described in this text is linked with Christology and ecclesiology.